Substrate engineering using naturally biomimicking corneal cell topography for preserving stemness of corneal limbal epithelial-stem cells - Tahereh Manoochehrabadi; Ali Samadikuchaksaraei; Amin Solouki; Seyed-Hashem Daryabari; Hamed Ghasemi; Ehsan Lotfi; Sajad Mansourian; Jila Majidi; Peiman Brouki Milan; Mazaher Gholipourmalekabadi (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Substrate engineering is one of the attractive fields of changing cell behavior and fate, especially for stem cell (SC) therapies. The SC pool is an essential factor in transplantation outcomes. Here, the objective was to preserve the stemness of the cornea’s limbal epithelial stem cell (LESC) using naturally biomimicking corneal cell topography.Materials and Methods: A cell-imprinted substrate was prepared using the natural topography of rabbit cornea’s LESC. The LESC cells were characterized by immunostaining (ABCG2 and Cytokeratin-12), then re-cultivated on a topography mold (imprinted PDMS), on FLAT PDMS (without any pattern), and the control group (tissue culture plate). Ultimately, an alkaline burn model was created on a rabbit’s cornea, and the effectiveness of cell-imprinted molds as implants for healing corneal wounds was examined in vivo.  Results: The in vitro results showed that imprinted PDMS kept LESC cells in a state of stemness with high expression of ∆NP63 and ABCG2 genes (stemness-associated genes) compared to the other two groups and low Cytokeratin-3 and -12 expression (as differentiation-related genes). In vivo studies showed a more significant number of cells and the expression of the ABCG2 gene in the imprinted PDMS group. In contrast, higher expressions of the ∆Np63 gene and more stratification were observed in the control group (no treatment). Histological studies showed that the imprinted PDMS group had normal morphology with fully organized collagens. Conclusion: The results of LESC cultured on imprinted PDMS suggested that LESC cell imprinting could be an excellent substrate for LESC expansion and preserve their stemness for cell therapy.